Mismatches between supply and demand in wildlife tourism: Insights for assessing cultural ecosystem services - (:unkn) unknown (My University, 2017)
Assessing cultural ecosystem services provided by biodiversity requires a combination of ecological and social approaches. In this study, we investigated the capacity of large African mammal species to provide the cultural ecosystem service of wildlife tourism by using a supply and demand framework. First, we tested the relationship between supply and demand for large mammal species in wildlife tourism. Second, we tested whether the trophic level and body size of mammals influenced the mismatch between supply and demand, and whether the patterns of mismatches were consistent among four protected areas (PAs) in three Southern African countries. To quantify supply of species, we counted large mammals along 196 five km road transects within the four PAs; to estimate demand, we gathered 651 face-to-face questionnaires of wildlife tourists and distinguished between their expectation and hope to see specific species. Results show that a higher supply of large mammal species increased the expectation to see a species (linear regression slope β = 0.28, p < 0.01), whereas supply did not affect the hopes to see a specific species (β = -0.04, p = 0.63). Analyses of mismatches revealed that predator species were more demanded in relation to their supply than ungulates. Finally, we found that the demands of wildlife tourists for mammal species in relation to their supply were consistent across the four PAs. Supply-demand analyses reveal that species’ traits, in particular trophic level, shape the hopes of wildlife tourists to see specific mammal species. We propose that the quantification of supply-demand mismatches can be used to identify charismatic species and relevant species’ traits, and can be applied for wildlife tourism assessments within as well as across regions. Supply-demand analyses provide a useful framework and deliver indicators for better assessing cultural ecosystem services involving wildlife and nature-based tourism, and can be used
Keywords: African Research